Synergy Between Legal and Child Protection Agencies in Juvenile Justice: Sinergitas Lembaga Hukum dan Perlindungan Anak dalam Peradilan Anak - Latumahina, Edy Janter; Sakalessy, Aleksander (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The juvenile justice system aims to protect children in conflict with the law, emphasizing restorative justice. Specific Background: In Indonesia, legal inconsistencies and weak inter-agency coordination hinder effective child offender rehabilitation. Knowledge Gap: There is limited research on optimizing synergy between law enforcement and child protection agencies in handling juvenile cases. Aims: This study explores mechanisms for enhancing collaboration in implementing diversion and restorative justice for child offenders. Results: Effective coordination improves outcomes by ensuring legal protections throughout the judicial process, supported by community-based restorative practices. Novelty: The research offers a model for integrating legal and social institutions to bridge gaps in policy and practice. Implications: Findings suggest policy refinements, enhanced law enforcement training, and integrated systems for protecting children’s rights. This study highlights collaborative approaches as vital for achieving justice and rehabilitation. Highlights: Restorative Justice Emphasis: Prioritizes rehabilitation and reconciliation over punitive measures for child offenders. Inter-agency Synergy: Highlights the importance of coordinated efforts between law enforcement and child protection agencies. Policy Implications: Advocates for enhanced legal frameworks, training, and integrated systems to uphold children's rights. Keywords: Law Enforcement, Child Protection Institutions, Criminal Offenders